Integrasi Nilai-Nilai Hukum Islam dalam Sistem Pendidikan Nasional Kajian Konseptual dan Implementatif - Rendi Fitra Yana; Ahmad Habin Sagala (Insan Zenius Ilmiah, 2025)
This study aims to formulate a conceptual and implementative framework for integrating Islamic legal values ​​into the Indonesian national education system. This is done as an effort to address the increasingly worrying character crisis and moral degradation among the younger generation. The national education system has so far prioritized a technocratic approach that tends to ignore the dimensions of values, ethics, and spirituality so that education loses its main function as a means of forming a whole person. The research method used is a qualitative approach with library research. An in-depth literature review was conducted on the basic principles of Islamic law, such as justice, responsibility, compassion, equality, and social solidarity, and their relevance in educational practices in Indonesia. The results of the study indicate that the integration of Islamic legal values ​​can be done through three main approaches, namely curricular, methodological, and cultural. Despite facing challenges in the form of ideological resistance, limited resources, and low-value literacy among educators, the development of a value-based curriculum, teacher training, and strengthening school culture can be effective solutions. This research makes an important contribution to the development of a more humanistic, character-based, and transcendental value-oriented national education.